Dragonbane - Kenyon, Sherrilyn 1965- (New York St. Martin's Press, 2015)
"Out of all the mysterious boarders who call Sanctuary home, no one is more antisocial or withdrawn than Maxis Drago. But then, it's hard to blend in with the modern world when you have a fifty foot wingspan. Centuries ago, he was cursed by an enemy who swore to see him fall. An enemy who took everything from him and left him forever secluded. But Fate is a bitch, with a wicked sense of humor. And when she throws old enemies together and threatens the wife he thought had died centuries ago, he comes back with a vengeance. Modern day New Orleans has become a battleground for the oldest of evils. And two dragons will hold the line, or go down in flames"--
"A Dark-Hunter novel"--Jacket
1
Keywords: Dragons -- Fiction; FICTION / Fantasy / Contemporary; FICTION / Fantasy / Paranormal; FICTION / Fantasy / Urban Life; FICTION / Romance / Fantasy; Good and evil -- Fiction; Fantasy fiction; Occult fiction